Comparison of Pulmonary Function Tests in Smokers and Non-Smokers (Medical Forum Monthly, 2024)
Purpose of Study: To compare the lung function tests in healthy non-smoker with age and sex matched smokers who are asymptomatic of respiratory impairment. Materials and methods: This cross sectional analytic study was carried out from June 2009 to November 2009 in Department of Medicine and Pulmonology, Jinnah Hospital, Lahore. A total of 200 subjects were included in the study. All individuals were selected from healthy general public visiting Jinnah hospital Lahore as attendants of the patients.FVC, FEV1 and FEV1/FVC were measured and recorded in Performa. Data was entered and analyzed in SPSS 10. Results: Mean age was 36.77+6.58 years. It was 34.11+7.38 in smokers and 33.43+5.39 in non-smokers group. Mean FEV1 was 2.55+0.79 in smokers and 3.52+0.55 in non-smokers. Mean FVC was 3.94+0.69 in smokers and 4.35+0.69 in non-smokes. Conclusion: Smoking causes significant reduction in lung functions in asymptomatic smokers which can be prevented by quitting smoking.